Improving newborn heart rate assessment using a simple visual timer. Issue 1 (6th May 2020) - Henry, Caroline; Morris, David E; Coleman, Sophie; Pereira, Andrea; Tamakloe, Christian; Blanchfield, Peter; Sharkey, Don
Abstract : Objective: Newborn resuscitation relies on accurate heart rate (HR) assessment, which, during auscultation, is prone to error. We investigated if a 6 s visual timer (VT) could improve HR assessment accuracy during newborn simulation. Design: Prospective observational study of newborn healthcare professionals. Setting: Three-phase developmental approach: phase I: HR auscultation during newborn simulation using a standard clock timer (CT) or the VT; phase II: repeat phase I after using a bespoke training app (NeoRate); phase III: following the Newborn Life Support course, participants assessed random HRs using the CT or VT. Main outcome measures: HR accuracy (within ±10 beats/min, correct HR category, i.e. <60, 60–100 and >100 beats/min), assessment time and error-free rates were compared. Results: Overall, 1974 HR assessments were performed with participants more accurate using the VT for ±10 beats/min (70% CT vs 86% VT, p<0.001) and correct HR category (78% CT vs 84% VT, p<0.01). The VT improved accuracy across all three phases. Additionally, following app training in phase II, the HR accuracy of both the CT and VT improved. The VT resulted in faster HR assessment times of 11 s (IQR 9–13) compared with the CT at 15 s (IQR 9–23, p<0.001). Error-free scenarios increased from 24% using the CT to 57% using the VT (p<0.001), with a shorter assessment time (CT 116 s (IQR 65–156) vs VT 53 s (IQR 50–64), p<0.001). Conclusion: Using a VT to assess simulated newborn HR combined with a training app significantly improves accuracy and reduces assessment time compared with standard methods. Evaluation in the clinical setting is required to determine potential benefits.